Cost effective technologies for solid waste and wastewater treatment - Kathi, Srujana; Devipriya, Suja; Thamaraiselvi, Kaliannan (Advances in environmental pollution research series, 2022)
Cost-Effective Technologies for Solid Waste and Wastewater Treatment synthesizes methods, case studies, and analyses of various state-of-the-art techniques for removing contaminants from wastewater, solid waste, or sewage and converting or reusing the waste with minimum impact on the environment. Focusing on innovative treatment strategies, as well as recent modifications to conventional processes, the book covers methods for a complex variety of emerging pollutants including organic matter, chemicals, and micropollutants resulting from developmental and industrial activities. Serving as a practical guide to state-of-the-art methods, Cost-Effective Technologies for Solid Waste and Wastewater Treatment also delivers foundational information on the practical design of treatment and reuse systems and explains the treatments in terms of scale, efficiency, and effectiveness. It focuses on cost-effective technologies that are particularly applicable to environmental clean-up, such as bioaugmentation and biostimulation of plastics, activated carbon, phytoremediation, crude oil pollution stress, adsorbents, contaminants of emerging concern, anaerobic digestion, in situ chemical oxidation (ISCO), biosorption, bioremediation, radioactive contaminants, constructed wetlands, nanoremediation, and rainwater. As such, it is a valuable and practical resource for researchers, students, and managers in the fields of environmental science and engineering, as well as wastewater management, chemical engineering, and biotechnology.